Posthumanism or Ecohumanism? Environmental Studies in the Anthropocene - Zapf, Hubert (Journal of Ecohumanism, 2022)
The paper discusses two of the currently most influential discourses in the environmental humanities, posthumanism and the Anthropocene, in the light of the concept of ‘ecohumanism’ suggested by the title of the present new journal. This concept resonates with the approach of a cultural ecology in literary studies and the environmental humanities, which takes an in-between stance between a radically ecocentric posthumanism and a narrowly anthropocentric humanism. The paper addresses four different domains in which such an ecologically redefined humanism can productively respond to some of the paradoxes and unresolved questions in current environmental studies: (1) the ambiguous role of science and the search for a valid basis of scholarly truth-claims; (2) the question of the subject, and of personal vs. impersonal agency; (3) the role of the archive and of the cultural past in Anthropocene thought and writing; and (4) the relation of the human and the non-human, and of the future of (eco-)humanism in the Anthropocene.